Material Culture and the History of Medicine in Shanghai, 1912-1949 - Zhang, Meishan (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2021)
From 1912 to 1949, especially under the administration of the Nanjing Government from 1927 to 1937, Shanghai witnessed drastic changes in its political structure, medical culture and social lifestyles through the construction of the public health system and intensive multicultural communication. How did people in Shanghai become acquainted with 'Western' medical equipment? What knowledge and daily practices did people accept along with the promotion of medical products? This thesis examines the sweeping changes in the material culture of Republican Shanghai by focusing on the production and adaptation of medical equipment, as well as the political, cultural and social variations proactively brought by politicians, medical professionals, intellectuals, the media and consumers. My dissertation demonstrates that no matter what identities and responsibilities people consider they have, they exert their subjective initiative to change their lives and social environment, whilst facing medical materials' potential challenges and opportunities.
APPROVED
Keywords: History of Medicine, Shanghai, Republican China, Material Culture